Antidepressant effects of a Persian herbal formula on mice with chronic unpredictable mild stress - Hakimeh Gavzan; Atefeh Araghi; Behrokh Marzban Abbasabadi; Nastaran Talebpour; Hannaneh Golshahi (Mashhad University of Medical Sciences, 2023)
Objective: Depression is a serious mental disorder. Despite numerous medications, there are still limitations in depression treatment. So, herbal medicine has been considered an alternative therapy. This survey evaluated the effects of a Persian herbal formula on mice with chronic unpredictable mild stress (CUMS).Materials and Methods: A combination of Aloysia triphylla  citrodora, Citrus aurantium, Echium amoneum, Lavandula angustifolia, Melissa officinalis, Salix aegyptiaca, Valeriana officinalis, Viola odorata, and Cinnamomum zeylanicum was prepared. Except for the control group, animals were subjected to CUMS for 8 weeks in 5 groups (n=10): CUMS, vehicle (distilled water), herbal formula (0.23 ml/mouse), fluoxetine (20 mg/kg), and bupropion (15 mg/kg). All administrations were performed orally daily for the last 4 weeks. The depression and anxiety-like behaviors were assessed by sucrose preference (SPT), tail suspension (TST), forced swimming (FST), and elevated plus-maze (EPM) tests. Superoxidase-dismutase (SOD) activities in tissues, and serum levels of cortisol, alanine-aminotransferase (ALT), and creatinine were measured. Also, histopathological changes were evaluated.Results: This formula significantly increased SPT (p<0.001) and decreased immobility time in FST and TST (p<0.01), but it was not effective on EPM vs. CUMS mice. The herbal formula did not change the serum level of creatinine or ALT, but insignificantly reduced cortisol vs. CUMS and vehicle groups. SOD activity increased in the brain vs. vehicle group (p<0.05). There were no changes in histological examination.Conclusion: The herbal formula improved depression-like behaviors which are possibly related to its anti-oxidative effect on the brain. Also, it did not cause any negative changes in the biochemical and histopathological analysis.